Focusing on positivity during the COVID-19 crisis: A New York health system strategy - Sven Gierlinger; Agnes Barden (The Beryl Institute, 2020)
In the midst of the COVID-19 pandemic, spreading positivity has become a core mission of Northwell Health, the largest integrated health system in New York. As a state and community health system, we are forever changed, but our need for compassion, humanism, and connection has never wavered. Creating innovative ways to bring humanity to the forefront, hope and optimism echo across the organization as initiatives, forums, and acts of gratitude have ensued. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens